Distribucion del blight en plantaciones de C. volkameriana, C. "Carrizo" y C. "Troyer" - Morales, M.=700 1 De Bernard, A.; Lima, H.
(Es, En)
Ilus., 12 ref.
Keywords: CITRUS VOLKAMERIANA; CITRUS SINENSIS; TIZON; ENFERMEDADES DE LAS PLANTAS; PLANTACIONES; CUBA; LIMONERO; NARANJA